Nova spoznanja o reninsko-angiotenzisko-aldosteronskem sistemu in nove strategije njegove zavore - Šušteršič, Matjaž (Medicinski razgledi, 2008)
The renin-angiotensin-aldosterone system is a hormone system chat is vital forthe regulation of arterial blood pressure, electrolyte balance and extracellular fluid volume in the body. Since the discovery of renin in 1898 and later the renin-angiotensin-aldostcronc system, there have been numerous studies on its effects and influences on physiological and pathophysiological mechanisms in different organs. The classical renin-angiotensin-aldosterone system pathway that begins with the release of renin from the kidneys, throughangiotensin-I, angiotensin-II and aldosteroneformation is a widely known concept that could now be described as incomplete. There is increasing evidence of the existence of a tissue renin-angiotensin-aldosterone system butit has been unsatisfactorily blocked with the blocking strategies known to dace. The objective of this paper is to address new knowledge about the renin-angiotensin-aldosterone system and new strategies for its blockage.
Keywords: Renin-Angiotensin System; Renin-angiotenzin, sistem; Aldosterone; Angiotenzin-pretvorba, encimski inhibitorji; Angiotensins; Aldosteron; Hypertension; Angiotenzini; Angiotensin-Converting Enzyme Inhibitors; Hipertenzija; Receptorji mineralokortikoidni; Receptors, Angiotensin; Receptorji, angiotenzin; Antagonists And Inhibitors; hormonski sistem; Receptors, Mineralocorticoid; arterijska hipertenzija; kardiologija; fiziologija; encimski inhibitorji